PENGEMBANGAN ASESMEN PORTOFOLIO BERBASIS SDGs UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS V PADA MATERI EKOSISTEM - Dwi Andriani, Dini; Hamdu, Ghullam; Ramadhani Putri, Agnestasia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Creative thinking is an important skill that can be taught in elementary school. The application of assessment is a key element in the learning process which is related to achieving student learning outcomes and plays a role in developing these skills. So this research aims to develop an SDGs-based portfolio assessment to improve creative thinking skills in the Ecosystem material for fifth grade elementary school students. The model used in research using the Design Based Research (DBR) research model consists of four stages, namely the Identification and Analysis of Needs stage, the design stage, the Trial or Implementation stage, and Reflection. Data collection techniques include interviews, documentation studies, expert validation sheets and student and teacher questionnaires. The results of the expert assessment validation test obtained a score of 83.3%, the learning tool expert validation obtained a score of 85.7% so it was categorized as "very feasible" and language validation obtained a score of 75% so it was categorized as "decent". From the implementation results, it was found that the implementation of the use of student portfolio assessments by assigning booklets, posters and waste recycling, can increase students' creative thinking. This can be seen from the 1st review to the 2nd review, there has been an increase in the score and percentage value for each aspect or indicator in the assessment framework. This is also supported by the positive responses of students and teachers from the results of questionnaires filled out by teachers and students.